The Seasonal and Meteorological Relationships of Diagnostic Distribution of Patients Presenting with Musculoskeletal Complaints According to Gender - Ayhan Kul; Mahir Uğur (Galenos Yayinevi, 2017)
Objective: The seasonal relationship of incidence of musculoskeletal system (MSS) pathologies according to gender and their meteorological variability has not been investigated satisfactorily. The aim of this study is to determine diagnostic distribution of patients with MSS-related complaints and the seasonal relationship of these diagnoses. Materials and Methods: This study was conducted on 45541 patients having MSS-related complaints. Female/male ratios of eleven diagnosis groups were considered and monthly/seasonal incidences were evaluated and relations with climatic factors were searched. Results: While number of patients for both genders admitted to polyclinics increased more in winter, lowest number of patients were admitted in summer. While knee-related pathologies were increased in April (9.4%) and rheumatologic disorders were increased in September (13.3%) for female patients, lumbar pathologies were most frequent in December (9.6%) and rheumatologic disorders were most frequent in September (13.0%) for male patients. Negative correlation was found between average temperature and knee pathologies for all the patients (r=-0.952, p=0.048). There were positive correlations between humidity and knee (r=0.980, p=0.020), elbow (r=0.951, p=0.049), hip (r=0.957, p=0.043), hand-wrist (r=0.963, p=0.037) and pathologies requiring rehabilitation (r=0.954, p=0.046). Conclusion: The number of admissions increased for both genders in winter months, and decreased in summer months. Moreover, relationships of some MSS pathologies with seasonal/meteorological changes should be considered.